The efficacy and tolerability of latency-reversing agents in reactivating the HIV-1 reservoir in clinical studies: a systematic review - Debrabander, Quinten; Hensley, Kathryn S.; Psomas, Christina K.; Bramer, Wichor; Mahmoudi, Tokameh; van Welzen, Berend J.; Verbon, Annelies; Rokx, Casper (Journal of Virus Eradication, 2023)
Understanding the clinical potency of latency-reversing agents (LRAs) on the HIV-1 reservoir is useful to deploy future strategies. This systematic review evaluated the effects of LRAs in human intervention studies. A literature search was performed using medical databases focusing on studies with adults living with HIV-1 receiving LRAs. Eligibility criteria required participants from prospective clinical studies, a studied compound hypothesised as LRA, and reactivation or tolerability assessments. Relevant demographical data, LRA reactivation capacity, reservoir size, and adverse events were extracted. A study quality assessment with analysis of bias was performed by RoB 2 and ROBINS-I tools. The primary endpoints were HIV-1 reservoir reactivation after LRA treatment quantified by cell-associated unspliced HIV-1 RNA, and LRA tolerability defined by adverse events. Secondary outcomes were reservoir size and the effect of LRAs on analytical treatment interruption (ATI) duration. After excluding duplicates, 5182 publications were screened. In total 45 publications fulfilled eligibility criteria including 26 intervention studies and 16 randomised trials. The risk of bias was evaluated as high. Chromatin modulators were the main investigated LRA class in 24 studies. Participants were mostly males (90.1%). Where reported, HIV-1 subtype B was most frequently observed. Reactivation after LRA treatment occurred in 78% of studies and was observed with nearly all chromatin modulators. When measured, reactivation mostly occurred within 24 h after treatment initiation. Combination LRA strategies have been infrequently studied and were without synergistic reactivation. Adverse events, where reported, were mostly low grade, yet occurred frequently. Seven studies had individuals who discontinued LRAs for related adverse events. The reservoir size was assessed by HIV-1 DNA in 80% of studies. A small decrease in reservoir was observed in three studies on immune checkpoint inhibitors and the histone deacetylase inhibitors romidepsin and chidamide. No clear effect of LRAs on ATI duration was observed. This systematic review provides a summary of the reactivation of LRAs used in current clinical trials whilst highlighting the importance of pharmacovigilance. Highly heterogeneous study designs and underrepresentation of relevant patient groups are to be considered when interpreting these results. The observed reactivation did not lead to cure or a significant reduction in the size of the reservoir. Finding more effective LRAs by including well-designed studies are needed to define the required reactivation level to reduce the HIV-1 reservoir.